PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X FASE E SMAN 2 PADANG - Assyura, Muhammad Hakim (Departemen Matematika, 2023)
General description of the results In 2023/2024, students in class X IPA E SMA Negeri 2 Padang had low mathematical problem solving skills, were less active, and less passionate about learning. The Problem Based Learning (PBL) model with Ice Breaking is used to overcome the weaknesses of direct learning. This study aims to test whether the implementation of PBL has superior abilities than the direct learning model and how they develop these abilities. In this descriptive quasi-experimental research, Static Group Design was used. The students studied were students in class X.E of SMA 2 Padang, specifically classes X.E 5 and 6. The t-test analysis of the mathematics problem solving ability test in the form of an essay showed a P-value of 0.001 at the α = 0.05 level. Because of this value, H0 is rejected, indicating that PBL is superior to direct learning. Based on the quiz scores, students' mathematical problem-solving skills improved.Keywords– Mathematical Problem Solving, PBL, Direct Learning